Analisis Penguatan Perlindungan Anak dari Eksploitasi Seksual Berbasis Daring dengan Kerjasama Kolaborasi Strategis antara UNICEF dan Pemerintah Indonesia - Kardina, Kardina; Afni, Nur (HUMAN: South Asian Journal of Social Studies, 2025)
Abstract. This article explores the strategic collaboration between UNICEF and the Government of Indonesia in addressing Online Child Sexual Exploitation and Abuse (OCSEA). Employing a descriptive qualitative approach and framed within the theories of human security and international cooperation, the study examines the implementation of the P-OCSEA program and the #JagaBareng digital campaign. The findings reveal that youth participation, public education, institutional capacity building, and policy development are central strategies in building a safe digital ecosystem for children. These efforts reflect a shift from reactive to preventive and community-based approaches. However, major challenges persist, including the absence of specific OCSEA legislation, limited child-friendly reporting mechanisms, low digital literacy in marginalized areas, and insufficient forensic training for law enforcement. The study highlights the need for sustained, multi-sectoral, and adaptive cooperation, supported by legal reforms, national curriculum integration, and active engagement from digital technology providers to ensure children's rights and safety in the evolving digital environment.